2010
DOI: 10.1111/j.1439-0426.2010.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Condition factor, length-weight and length-length relationships of an endangered fish Ompok pabda (Hamilton 1822) (Siluriformes: Siluridae) from the River Gomti, a tributary of the River Ganga, India

Abstract: The present study describes the condition factor, length-weight and length-length relationships for an endangered freshwater fish species Ompok pabda (Hamilton) of the family Siluridae from the River Gomti in Northern India. The values of regression parameter b ranged from 2.81 to 3.32 (r 2 > 0.90). During the pre-monsoon, the allometric coefficient b of the LWR was close to isometric value (b = 3.08) allometric (b = 2.87), although it suggested negative allometric growth in monsoon periods while positive grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 5 publications
2
17
1
1
Order By: Relevance
“…The Kenyan IUCN red list threatened fishes biometric information has been quite insufficient despite a number of studies having been conducted within the Asian countries (Hossain et al, 2012;Gupta et al, 2011;Muchlisin et al, 2010;Naeem et al, 2010Naeem et al, , 2011Patiyal et al, 2010;Sani et al, 2010;Sarkar et al, 2009;Yousaf et al, 2009). In this study, the 10 species size structures demonstrated some marked length size class range differences (Table 1).…”
Section: Discussionmentioning
confidence: 78%
“…The Kenyan IUCN red list threatened fishes biometric information has been quite insufficient despite a number of studies having been conducted within the Asian countries (Hossain et al, 2012;Gupta et al, 2011;Muchlisin et al, 2010;Naeem et al, 2010Naeem et al, , 2011Patiyal et al, 2010;Sani et al, 2010;Sarkar et al, 2009;Yousaf et al, 2009). In this study, the 10 species size structures demonstrated some marked length size class range differences (Table 1).…”
Section: Discussionmentioning
confidence: 78%
“…The present CF f value of G. cenia (0.74±0.005) is out of range (1.62±0.28 to 2.01±0.26) report by Chaki et al (2013) may be due to food staff and gonad maturation (Gupta et al, 2011). BW r is used to know the prey availability, food abundance and sexual maturity of fishes (Anderson and Neumann, 1996).…”
Section: Resultsmentioning
confidence: 96%
“…A 1.20 value of K indicates that the fish is of moderate condition and acceptable to many anglers. A Gupta et al (2011) the difference in condition factor could be due to the availability of food organisms at a particular time as well as the difference of gonad development. The present data could not clarify which factors among those described above could have led to these observations.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the length-weight relationship and condition factor have been well documented in many tropical freshwater fishes including the golden mahseer, Tor putitora, striped dwarf catfish, Mystus vittatus, butter catfish, Ompok pabda and scissor-tail rasbora, Rasbora tawarensis (Gupta et al 2011;Hossain et al 2006;Muchlisin et al 2010;Zafar et al 2002). Several studies on freshwater fish species in Malaysia have also been conducted in Sungai Batu and Sungai Tua in Selangor, Chenderoh and Kerian River basin in Perak, Pedu Lake in Kedah and Kenyir Reservoir in Terengganu (Kamaruddin et al 2012;Mansor et al 2010).…”
Section: Introductionmentioning
confidence: 99%